Factors affecting employee commitment in Molnlycke Health Care Sdn. Bhd. / Nurazlinda Abdul Razak and Mohammad Nazmee Abdul Razak - Abdul Razak, Nurazlinda; Abdul Razak, Mohammad Nazmee (2018)
This chapter focuses on the background of this study which is employee commitment in manufacturing industry. It introduces the overall concept of employee commitment, and followed by problem statement, research question, research objectives, scope of study, significant of the study, and the definition of key terms and concepts that is used in this study.